Milnor number and chern classes for singular varieties: An introduction - Callejas-Bedregal, Roberto; Morgado, Michelle F.Z. [UNESP]; Seade, José (Springer Nature, 2022)
We survey how the Milnor number of complex map-germs with an isolated critical point relates to various indices of vector fields on singular varieties, and the way how this number extends via the theory of Chern classes of singular varieties, to the concept of Milnor classes of varieties with arbitrary singular set in complex manifolds. This relates several deep theories in mathematics and gives rise to a necklace of beautiful jewels.